Development and Validity Analysis of an ESP8266-Based IoT Training Kit for Vocational School Students - Habibi, Mohammad Wildan (Juwara: Jurnal Wawasan dan Aksara, 2025)
The transformation of vocational education, especially vocational high schools (SMK), towards Industry 4.0 requires learning media in the field of IoT that are affordable, applicable, and aligned with the curriculum. This study aims to develop and analyze the validity of an ESP8266-based IoT training kit for vocational school students. Using the Borg & Gall Research and Development model, the stages include needs analysis through practical observations and teacher interviews, design and prototype creation, and expert validation. Three validators (experts in learning media, vocational education learning, and one vocational school teacher in the field of electronics) assessed the kit using a Likert scale of 1-4 with a calculation of the percentage of achievement. The results showed an average validity of 98%, so the product is classified as very valid and suitable for use as a learning medium. Theoretically, this study strengthens research on the development of IoT media in vocational education. On the other hand, practically, the resulting training device is very economical, simple, compatible with various sensors/actuators, and facilitates students' application skills through direct practice. The implication is that this training tool is ready to be integrated into practical sessions to support the achievement of IoT competencies and job readiness.